Interlingual and Intralingual Interferences in EFL Students’ Writing: A Case Study at Aphrodite English Club - Rahmawati, Rida; Mala Rohmana, Wahyu Indah (Beyond Words, 2023)
This study aims to determine the type and the factors of interference that occur in EFL students' writing. This research used a qualitative method with a case study research design in this study. The subjects of this study consisted of one writing skills teacher and 6 grade 3 students from the Aphrodite English Club. In collecting data, there are three research instruments used, i.e., observation, documentation analysis, and interviews. Then, the data will be analysed using three ways of data reduction, presenting the data in tabular and transcript form and the last step is making conclusions. The results showed that the type of interference often occurs in EFL students is interlingual interference; students make many grammars error that occurs because of the influence of the structure of the first language on the target language. In intralingual interference, students made many mistakes in incomplete language structures, including the absence of appropriate sentence prepositions. Two factors are behind interference, i.e., the internalisation of culture and the student's lack of motivation to study writing in English.